Workplace Unionism, Collective Bargaining and Skill Formation: New Results from Mixed Methods - Fabio Berton; Anna Carreri; Francesco Devicienti; Andrea Ricci (Institute of Labor Economics (IZA), 2019)
Among the steps to improve a country's competitiveness, several commentators and international institutions include a general emphasis on deregulation and decentralization of industrial relations. In this paper, we contribute to this debate by studying whether and how firm-level unionism and collective agreements affect workplace training, a key ingredient to competitiveness. Theory provides inconclusive predictions on the various channels and processes through which firm-level industrial relations may affect workplace training. Quantitative and qualitative analyses, when used in isolation, have also proved insufficient for an adequate account of the various factors at play. This is where our paper mostly contributes. In the spirit of opening the "black box" of firm-level unionism and collective bargaining, we mix together quantitative and qualitative strategies. Our results suggest that workplace unionism, and especially decentralized collective agreements, favor workplace training in subtler and often more dynamic ways than commonly understood.
Keywords: J24; J52; 330; workplace training; industrial relations; firm-level bargaining; Italy